THE UTILIZING SOCIAL MEDIA STRATEGIES ON INCREASING THE PROSPECTIVE STUDENTS' INTEREST AT STIT TOGO AMBARSARI BONDOWOSO - Sahrotul Qeisiyeh (Evaluasi : Jurnal Manajemen Pendidikan Islam, 2025)
The New Student Admissions (NSA) at STIT Togo Ambarsari (STITTA) Bondowoso utilizes social media platforms as a promotional tool to attract prospective students. This study aims to analyze the strategies of social media utilization in increasing the interest of prospective students at STITTA. This research uses a qualitative approach with data in the form of sentences, sourced from lecturers, educational staff, and students. The data collection methods include observation and active engagement techniques, where the researcher listens to the statements of lecturers, educational staff, and students during the NSA process and records and notes relevant information. Additionally, the researcher conducts interviews with lecturers, educational staff, and students to gain deeper insights into the research objectives. Once the data is collected, the researcher transcribes the recorded statements into written form. Next, the researcher conducts data reduction by selecting and sorting the statements relevant to the research objectives, classifying the data by type. Data validation is carried out through consultation with lecturers to ensure the accuracy and reliability of the collected data. After that, the data is analyzed through tabulation by assigning codes to each data point, which are then interpreted to draw conclusions. The research findings indicate that the strategy for utilizing social media to increase the interest of prospective students at STITTA consists of three main stages: planning, implementation, and evaluation. In the planning stage, a NSA committee is formed, and ideas or concepts for relevant, valid, and accountable content are developed to help prospective students easily find the information they need. In the implementation stage, social media is used to share the prepared content across various platforms, including Facebook, Instagram, TikTok, WhatsApp, and YouTube. In the evaluation stage, each activity shared is monitored to assess its effectiveness, which is then used as feedback for improving the use of social media for future NSA processes.